Facilitating Pre-Service Teachers’ Writing Skills Through Scaffolding-Based Instruction - Elyza, Ferlya; Haliq, Abdul; Lubis, Silvi Puspa Widya (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. The study aims to find the effectiveness of Scaffolding-Based Instruction (SBI) for teaching writing in the context of higher education and capture the process of an SBI in genre-based EFL writing for English department students in higher education to improve students’ writing skills. The study was grounded in Design-Based Research (DBR) (Akker et al., 2006) and Participatory Action Research (PAR) (Kemmis& McTaggart, 2005).  PAR was placed at the third phase of DBR in iterative cycles of testing and refinement of solutions in practice. It purposes to develop and improve the model for its appropriateness. The study was conducted in two private universities, the University of Abulyatama (UNAYA) and Universitas Bina Bangsa Getsampena (UBBG), in the Province of Aceh. Two teacher collaborators and 57 students volunteered to participate in the study. The data were collected through observation, questionnaire and interview. Data analysis was carried out descriptively and the effectiveness during Teaching Learning Cycles (TLC) was analyzed through the average score between the pre-test and post-test.  The result of the study revealed that the SBI model implemented in the Intermediate Writing class was effective after the teaching-learning cycle in the form of PAR it shows a difference between the pre-test and post-test scores with an average of 42.81 to an average of 69.31. Based on the evaluation results, SBI learning models and tools can be implemented in learning to write argumentative essays by paying attention to suggestions and comments given by potential users. SBI learning model is innovative and typically support and promote collaborative learning that carried out learning based on the 4C’s of 21st-century skills (critical thinking, creativity, collaboration, and communication). It implies to students’ self-directed learning paradigm to self-determined learning paradigm.Keywords: writing, genre-based approach, scaffolding